Dynamical mechanism of tacit knowledge dissemination based on newman-watts network - Liang, Qianqian; Guo, Lingling; Shen, Jianwei (Frontiers in Physics, 2022)
The diffusion of tacit knowledge subjects has an essential influence on tacit knowledge dissemination. The introduction of diffusion in the traditional diffusion model does not lead to change in the dynamical behavior of the diffusion system. In this study, tacit knowledge dissemination model is proposed by using a SIR model. The stable dissemination conditions of tacit knowledge are clarified through the stability analysis and network dynamics analysis. According to the characteristics of enterprise alliance, Newman-Watts(NW) networks are constructed to study the role of diffusion between knowledge learners and knowledge disseminators in periodic and local dissemination. The influence of network structure on the dynamical behavior of the network organization system is shown by the network structure entropy(NSE). The results indicate that network structure entropy and diffusion can induce the emergence of both periodic and local dissemination behaviors. The diffusion of knowledge learners becomes the key factor of periodic dissemination. This model reveals the dissemination mechanism of tacit knowledge, which can guide significance for effectively accelerating tacit knowledge dissemination and improving the core competitiveness of the enterprise.